Hubungan Pola Asuh Orang Tua dengan Kematangan Emosi Pada Remaja Kelas III di SMP Negeri 1 Kuta Badung Bali - Ni Putu Galih Prestina Neda; I Wayan Eka Arsana; Dewa Ayu Agung Alit Suka Astini (Aesculapius Medical Journal, 2022)
Adolescence experience very intense emotional dynamics, hence why teenagers should reach emotional maturity to be able to control their emotions. Students in 3rd grade are considered in the early teen category, where in this stage teenagers are prone to emotional instability. If not guided properly, this emotional instability could cause negative effects. In the process of emotional maturity, parenting style plays a significant role that according to Hurlock are divided into three, democratic, authoritarian, and permissive. This study aims to discover the relationship between parenting styles on emotional maturity in third grade students at SMP Negeri 1 Kuta. The design of this study is a cross sectional with correlational quantitative approach. Subjects on this study are 157 students who are currently in grade III studying at SMP Negeri 1 Kuta. The independent variable in this study is parenting styles, and the dependent variable is emotional maturity. This study uses questionnaires on parenting styles and emotional maturity scales. Data was analyzed in descriptive form and statistical with Spearman rank correlation test. This study finds the following percentage of parenting styles, democratic (91.7%), authoritarian (8.3%), and permissive (0%). Meanwhile, the following are the percentage of emotional maturity found in this study, intermediate (82.8%), high (10.2%), and low (7%). Analysis results with Spearman rank correlation test showed a significance level of (p-value) < 0.05 (p = 0.0002), and a correlation coefficient (r) of 0.224. In conclusion, the majority of the subjects experience a democratic parenting style, has an intermediate emotional maturity, also analysis statistiic results showed that there is a positive correlation with a low rate of correlation between parenting styles and emotional maturity in teenagers.